Dose-response relationship between serum uric acid levels and risk of incident coronary heart disease in the Dongfeng-Tongji Cohort. (1st December 2016) - Lai, Xuefeng; Yang, Liangle; Légaré, Sébastien; Angileri, Francesca; Chen, Xuguang; Fang, Qin; Yang, Handong; Zhang, Ce; Li, Xiulou; Min, Xinwen; Xu, Chengwei; Yuan, Jing; et al.
Abstract: Background: In prospective studies, relationship of serum uric acid (SUA) with risk of coronary heart disease (CHD) incidence is inconsistent. We evaluated the association of SUA with incident CHD and the potential modifying effect of major CHD risk factors related to SUA among a middle aged and elderly Chinese population. Methods: We included 16, 063 participants who were free of CHD, stroke, cancer and renal diseases at baseline from Sep. 2008 to June 2010, and were followed until Oct. 2013. Cox proportional hazard model was used to estimate the hazard ratios (HR) and 95% confidence interval (95% CI) of CHD incidence in relation to SUA. Results: The adjusted HR for incident CHD increased gradually with the increasing SUA levels ( P for linear trend = 0.005), and the HR across sex-specific SUA quartile was 1.26 (95% CI: 1.09, 1.47), 1.13 (95% CI: 0.97, 1.31), 1.23 (95% CI: 1.06, 1.43) and 1.00 (reference; P for trend = 0.014), respectively. In particular, the association was more evident in individuals with normal-weight and those without hypertension or metabolic syndrome (all P for interactions < 0. 05). Conclusions: These findings suggested that higher SUA levels were independently associated with a dose-response increased risk of CHD incidence. Highlights: Hyperuricemia is confirmed as an independent risk factors for incident coronary heart disease. Serum uric acid is independently associated, in a dose-response manner, with incident coronary heart disease. The association might be modified by hypertension, overweight, and metabolic syndrome.